The Cyber Risk Handbook Creating and Measuring Effective Cybersecurity Capabilities - Antonucci, Domenic (Ascent Audio, 2024)
The Cyber Risk Handbook is the practitioner's guide to implementing, measuring, and improving the counter-cyber capabilities of the modern enterprise. The first resource of its kind, this book provides authoritative guidance for real-world situations and cross-functional solutions for enterprise-wide improvement. Beginning with an overview of counter-cyber evolution, the discussion quickly turns practical with design and implementation guidance for the range of capabilities expected of a robust cyber risk management system that is integrated with the enterprise risk management (ERM) system. Expert contributors from around the globe weigh in on specialized topics with tools and techniques to help any type or size of organization create a robust system tailored to its needs. Chapter summaries of required capabilities are aggregated to provide a new cyber risk maturity model used to benchmark capabilities and to road-map gap-improvement. Cyber risk is a fast-growing enterprise risk, not just an IT risk. Yet seldom is guidance provided as to what this means. This book is the first to tackle in detail those enterprise-wide capabilities expected by board, CEO, and internal audit, of the diverse executive management functions that need to team up with the information security function in order to provide integrated solutions.
Audio book. - Online resource; title from title details screen (cloudLibrary, viewed November 28, 2024)
Keywords: Computer crimes; Business enterprises -- Computer networks -- Security measures; Cyberspace -- Security measures; Business -- Data processing -- Security measures; Risk management; Criminalité informatique; Gestion; Informatique; Sécurité; Mesures; Gestion du risque; risk management; Financial Risk Management; Finance; BUSINESS & ECONOMICS; Audiobooks; Livres audio